Complete Oral Nutritional Supplements: Dietitian Preferences and Clinical Practice. (2nd January 2019) - Uí Dhuibhir, Pauline; Collura, Noelle; Walsh, Declan
ABSTRACT: Oral nutritional supplements (ONS) are frequently prescribed for those at risk of malnutrition. Palatability is an important factor in long-term compliance. ONS selection is typically dietitian led, but the degree to which individual perceptions of palatability influence dietitian clinical decision making is unclear. This study aimed to explore factors that influence dietitians' ONS clinical practice, evaluate dietitian hedonic preferences and overall impression of specific ONS products, and study phenylthiocarbamide (PTC) sensitivity in relation to ONS hedonic ratings. Dietitians were recruited from six urban teaching hospitals. They completed a 10-item Clinical Practices Questionnaire prior to taste testing five samples of three ONS products. A 7-point hedonic Likert scale recorded ONS palatability ratings. A PTC test was conducted. Thirty-one dietitians were recruited. Nutritional value, patient palatability, patient acceptability, tolerance and hospital contracts were the factors identified as most likely to influence ONS prescription. All ONS were consistently highly rated for overall impression. The high-protein ONS was most highly rated for all hedonic characteristics. Taste was the highest rated hedonic characteristic across all products. No statistically significant relationship was found between PTC sensitivity and ONS overall impression. The key drivers of ONS dietitian clinical practice were identified. ONS hedonic characteristics and overall impression were highly rated, which suggested this range of products had wide appeal for dietetic professionals. The taste and consistency of the ONS were rated better than other hedonic characteristics (appearance, smell, aftertaste).